Financing democracy - Gersbach, Hans; Liessem, Verena (CESifo working papers, 2002)
Based on contribution patterns to parties in Germany and elsewhere, we suggest that democracies should use a mixed system where private funding can play a larger role than public funding. In Germany the high level of public funding for parties can be reduced without expecting undesirable effects if the parties are forced to increase private funding. Private contributions can be unlimited but tight transparency requirements on private funding are necessary. This can be achieved by setting up an independent commission with institutionalized publication rules. Tax deductibility of private contributions should be eliminated.